Production and characterization of a new detergent-stable keratinase expressed by Pedobacter sp. 3.14.7, a novel Antarctic psychrotolerant keratin-degrading bacterium - Rios Cruz, Patricia Leonela; Bezus, Brenda; Cavalitto, Sebastian Fernando; Cavello, Ivana Alejandra (Journal of Genetic Engineering and Biotechnology)
Background: Antarctica is one of the harshest environments in the world. Despite this fact, it has been colonized by microorganisms, which had to develop different adaptations in order to survive. By studying their enzymes, we can harness these adaptations in order to use them in various industrial processes. Keratinases (E.C. 3.4.99.11) are characterized by their robustness in withstanding extreme conditions and, along with other enzymes, are commonly added to laundry detergents, which makes their study of industrial interest. Results: In this work, a novel keratinase producer, Pedobacter sp. 3.14.7 (MF 347939.1), isolated from Antarctic birds’ nests, was identified. This psychrotolerant isolate displays a typical psychrotolerant growth pattern, with an optimal temperature of 20 °C (μmax=0.23 h−1). After 238 h, maximum proteolytic (22.00 ± 1.17 U ml−1) and keratinolytic (33.04 ± 1.09 U ml−1) activities were achieved with a feather sample conversion of approximately 85%. The keratinase present in crude extract was characterized as a metalloprotease with a molecular weight of 25 kDa, stable in a wide range of pH, with an optimum pH of 7.5. Optimum temperature was 55 °C. Wash performance at 20 °C using this crude extract could remove completely blood stain from cotton cloth. Conclusion: We report a new keratinolytic bacteria from maritime Antarctica. Among its biochemical characteristics, its stability in the presence of different detergents and bleaching agents and its wash performance showed promising results regarding its potential use as a laundry detergent additive. Fil: Rios Cruz, Patricia Leonela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Bezus, Brenda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...